Studi Unsur Radioaktif Thorium (Th) dan Uranium (U) di Pulau Bangka - Irvani Irvani; Janiar Pitulima (PROMINE, 2017)
As one of the island that producing tin ore mineral (cassiterite), Bangka Island has probably a bigpotential of tin associated mineral that contains radioactive elements like Thorium (Th) and Uranium(U). Th and U can be one of potential future prospect elements expecially for nuclear energy. Th andU elements bearing minerals in Bangka Island not yet exploited. They take out from the tin ore miningand becoming tailing, and then through the surface water flows or shallow sea water as sediment. Thestudy goal is to getting the number of radioactive Th and U elements using surface sediment sampleand then interpretation some part of their spatial distribution form. The Surface sediment data hasbeen collected on 2 sites Kolong in Muntok District West Bangka Regency, 3 sites in MerawangDistrict Bangka Regency, 9 sites in Pangkalpinang City, 2 sites in Central Bangka Regency and 2sites in South Bangka Regency. Chemistry analysis of sediments for identification the presence of Thand U elements. Radioactive element of Uranium (U) almost presence at all shallow surfacesediment 4.842 - 229.2 ppm except nul in 1 sample. Thorium (Th) just presence in a part of sedimentsample. One site as especially case study Kacang Pedang Retention Ponds, shows Th and Uradioactive elements has the heterogenity spatial pattern.